2007
DOI: 10.1539/joh.49.88
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size of Intratracheally Instilled Crystalline Silica on Pulmonary Inflammation

Abstract: Effect of Particle Size of IntratracheallyInstilled Crystalline Silica on Pulmonary Inflammation: Takayoshi KAJIWARA, et al. Department of Environmental Health Engineering, University of Occupational and Environmental HealthCrystalline silica, known as a causal substance of silicosis, has been carefully evaluated for its carcinogenicity and fibrogenicity. In this study, we instilled crystalline silica of two different size (S 1.8 :1.80 µm (S.D. 2.0), S 0.7 :0.74 µm (S.D. 1.5)) into the trachea of rats to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
0
25
1
Order By: Relevance
“…In human beings, toxicity becomes very important when aerodynamic diameter of the particles is 10 μm, which enables them to reach the pulmonary alveoli. In rats and mice, this value approximates 2 μm for intratracheally instilled silica (Wiessner et al, 1989; Takayoshi et al, 2007). The ROFA used in the present study was mainly composed of particles bigger than 10 μm (Avila et al, 2011), which would be less harmful than the smaller ones (Donaldson et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…In human beings, toxicity becomes very important when aerodynamic diameter of the particles is 10 μm, which enables them to reach the pulmonary alveoli. In rats and mice, this value approximates 2 μm for intratracheally instilled silica (Wiessner et al, 1989; Takayoshi et al, 2007). The ROFA used in the present study was mainly composed of particles bigger than 10 μm (Avila et al, 2011), which would be less harmful than the smaller ones (Donaldson et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…Particle size and surface area can play important roles in the response to inhaled particles, which is especially relevant for ultrafine or nano particles [1][2][3] . Our previous study using crystalline silica showed that even if the particles are of the same chemical composition, their biological effects vary depending on their particle size 4) . Hazard assessment of newly-generated respirable particles must therefore be conducted for such differences and various biomarker studies are currently being implemented to objectively and quantitatively assess the hazards of such substances [5][6][7][8][9][10][11][12][13][14] .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Moreover, the majority of studies investigating the fate of inhaled nanomaterials have been based on examining the lung clearance kinetics of the drug, rather than the polymer or polymer-drug conjugate. The critical issue here is that the safety of inhaled polymer-drug conjugates has also been called into question, based on widespread literature suggesting that nanomaterials, albeit nonbiodegradable/non-biocompatible nanoparticles, are 'toxic' in the lungs [16][17][18][19][20]. It is therefore important to understand the rate and mechanisms of polymer clearance from the lungs in order to design optimal dosing schedules that limit the long term retention of the polymer in the lungs and the potential for local adverse effects.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It has been widely demonstrated that environmental pollutants including particulate material, inorganic/metal nanoparticles and non-biodegradable polymeric nanoparticles are capable of inducing inflammation, oxidative stress, cytotoxic and genotoxic effects in the lungs after inhalation [16][17][18][19][20]. In contrast, however, very few studies have been carried out to determine the immunological, inflammatory and toxicological potential of inhalable polymer drug conjugates or biodegradable polymers which have potential for pulmonary application.…”
Section: Current Opinion On the Future Of Inhalable Polymer-drug Conjmentioning
confidence: 99%